Brideshead revisited [videorecording (DVD)] / Miramax Films UK Film Council and BBC films present. - Waugh, Evelyn, 1903-1966; Thompson, Emma; Gambon, Michael (Miramax, 2009)
A Londoner of lower class befriends and begins a romantic relationship with an aristocrat that becomes complicated when the aristocrat introduces his new friend to his sister.